2009
DOI: 10.1007/s00167-009-0973-z
|View full text |Cite
|
Sign up to set email alerts
|

Is there any superiority in the clinical outcome of mobile-bearing knee prosthesis designs compared to fixed-bearing total knee prosthesis designs in the treatment of osteoarthritis of the knee joint?

Abstract: To substantiate the validity and relevance of the mobile-bearing knee prosthesis design compared to the fixed-bearing design, concerning the clinical outcome, this review was conducted. Articles published in 6 major orthopaedic journals were screened. Only randomized controlled trials, which investigate the clinical outcome, were included. The clinical outcome parameters of each study were analysed. Despite the numerous quantities of publications in orthopaedic literature, we could conclude, that only a few of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 44 publications
3
18
0
Order By: Relevance
“…In the 6 to 10 year (median 7.9 years) follow-up study the mobile bearing knees did not sustain the difference in AKP that had been found in the short-term study [12,13] . These results are comparable to the findings of other systematic reviews and/or meta-analysis, most of which have not shown an advantage of using a mobile bearing [22,36,[48][49][50][51] . Based on these results combined with a recent metaanalysis showing less AKP in the mobile bearing TKA, it seems that the debate can be reopened as to whether the mobile bearing TKA is part of the solution to AKP [52] .…”
Section: Regeneration Of Nervessupporting
confidence: 87%
“…In the 6 to 10 year (median 7.9 years) follow-up study the mobile bearing knees did not sustain the difference in AKP that had been found in the short-term study [12,13] . These results are comparable to the findings of other systematic reviews and/or meta-analysis, most of which have not shown an advantage of using a mobile bearing [22,36,[48][49][50][51] . Based on these results combined with a recent metaanalysis showing less AKP in the mobile bearing TKA, it seems that the debate can be reopened as to whether the mobile bearing TKA is part of the solution to AKP [52] .…”
Section: Regeneration Of Nervessupporting
confidence: 87%
“…Some studies have compared all mobile-bearing subtypes as a single cohort with fixed-bearing designs [4,5,33]; some meta-analyses performed the same comparison as a result of the availability of data [17,24,28,37,38,41,42]. Six of the meta-analyses comparing mobile-bearing and fixedbearing prostheses that we reviewed in preparation for our meta-analysis found no significant differences in The Knee Society scores, Hospital for Special Surgery scores, ROM, radiolucent lines, prosthesis-related complications, or patient preference [24,27,28,37,38,42].…”
Section: Discussionmentioning
confidence: 99%
“…The results after primary knee arthroplasty are reasonably predictable and reproducible [6,11,19,35,38]. Revision knee arthroplasty is a technically and economically demanding procedure [8,23,39] and is usually associated with worse results than after primary arthroplasty [3,7,15,17,28].…”
Section: Introductionmentioning
confidence: 99%